Cloud computing for enterprise architectures - Hill, Richard; Mahmood, Zaigham (Computer communications and networks, 2011)
Focuses on cloud computing design and implementation techniques. This book examines cloud computing from the perspective of enterprise architecture, asking the question; how do we realize new business potential with our existing enterprises? It presents the architecture approaches with respect to cloud computing models and frameworks